Utilization of Crumbs from Discarded Rubber Tyres as Coarse Aggregate in Concrete: A Review - Eze, Val Hyginus Udoka; Uche, Chikadibia Kalu Awa; Chinyere, Ugwu; Wisdom, Okafor; Chukwudi, Ogenyi Fabian (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This research work successfully reviewed twenty-five papers on waste rubber tyres and their related areas. The chemical and physical properties of concrete constituents such as cement, water, sand and rubber crumbs were reviewed together with their mix ratios. The use of Tyre Rubber Crumbs (TRC) to replace coarse aggregates makes concrete construction work cheaper and its low water absorption rate improves the concrete mix properties such as compressive strength and workability. Hence, in road pavement construction, the use of TRC in asphalt modification is the best and smartest innovation for sustainable development and waste material reuse. This research showed that waste TRC are very essential in the replacement of some aggregates in the construction industries resulting in very high-quality construction and as well minimize construction costs.